2018
DOI: 10.1111/dom.13572
|View full text |Cite
|
Sign up to set email alerts
|

Follistatins in glucose regulation in healthy and obese individuals

Abstract: Aims It has been suggested recently that follistatin (FST) and its homologous protein, follistatin‐like 3 (FSTL3), may be a therapeutic target in the treatment of type 2 diabetes because of their glucose‐regulatory effects in rodents. Materials and Methods We investigated this hypothesis in humans by studying the physiology of a possible glycaemia–follistatin feedback loop, that is, whether glucose, but not lipid intake (oral or intravenous), can regulate circulating FST and FSTL3 in healthy humans (n = 32), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
3
20
2
Order By: Relevance
“…Previous studies have shown that circulating FST is higher in patients with T2D than in glucose-tolerant individuals or obese individuals and that activin A levels are similar between these groups (Perakakis et al, 2019;Sylow et al, 2020). However, our results indicated that the level of serum FST was lower in patients with diabetic cardiomyopathy than in healthy individuals, and the in vitro experimental results also verified this finding.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that circulating FST is higher in patients with T2D than in glucose-tolerant individuals or obese individuals and that activin A levels are similar between these groups (Perakakis et al, 2019;Sylow et al, 2020). However, our results indicated that the level of serum FST was lower in patients with diabetic cardiomyopathy than in healthy individuals, and the in vitro experimental results also verified this finding.…”
Section: Discussionsupporting
confidence: 86%
“…Follistatin is mainly secreted by the liver and its inactivation in hyperglycemic mice improves glucose homeostasis by reducing insulin resistance [18]. We have recently demonstrated that glucose or the concomitant insulin release during OGTT reduces follistatin levels, suggesting the presence of a feedback loop mechanism controlling the effects of follistatin on glucose metabolism [16]. In line with these findings, we have also reported a reduction of follistatin in morbidly obese patients early after bariatric surgery, which predicts the improvement in insulin sensitivity observed later in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from adaptations in post-prandial gut peptide responses, additional humoral mechanisms may contribute to the restoration of insulin sensitivity following surgery. Perakakis et al have recently shown that reduced circulating follistatin levels 3 months after RYGB or VSG are able to predict improvements in fasting plasma glucose (FPG), glycated hemoglobin (HbA1c) and insulin resistance 12 months post-operatively, both in individuals with and without T2DM [34]. Additional factors with a presumed weight-loss-independent role in metabolic improvement post-surgery include increased glucose utilization from the intestine, and alterations of gut microbiota [35].…”
Section: Mechanisms Of Type 2 Diabetes Mellitus (T2dm) Remission Fmentioning
confidence: 99%